Pengaruh literasi ekonomi dan literasi digital terhadap kemampuan spesifik mahasiswa dalam berwirausaha - Corniatin indri sholespy; Agung Haryono (Jurnal Pendidikan Ekonomi, 2022)
Entrepreneurship attracts many students because it can improve the Indonesian Economy and create jobs. However, there are some students who fail in entrepreneurship, this can be influenced by several factors. Among them is an understanding of economic knowledge and digital knowledge. For this reason, this study aims to determine the Effect of Economic Literacy and Digital Literacy on Students' Specific Abilities in Entrepreneurship in the S1 Study Program of Economics Education, Faculty of Economics, State University of Malang. The population in this study were all undergraduate students of economic education with the sample calculation using the Slovin formula. The sampling technique used purposive random sampling. By using multiple linear regression analysis resulted that partially and simultaneously the variables of economic literacy and digital literacy have a positive effect on the specific ability of students in entrepreneurship. This is influenced by students' understanding of economics and entrepreneurship theory that have been studied in courses that have been taught in the previous semester.DOI: https://dx.doi.org/10.17977/UM014v15i22022p105